N Nilai Pendidikan Pada Lontar Cakragni dan Relevansinya di Masa Pandemi Covid-19 - Anggun Wendraswari (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
The Covid-19 pandemic has caused tremendous fear for the world community, including Indonesia. One of the impacts of this Covid-19 is education in Indonesia . Since the Lock Down policy was implemented, all students had carried out online learning activities from home, of course, affecting students' understanding of religion, especially old literary or literary works. For the Balinese lontaris considered a library that stores sacred religious teachings, besides that it is used as a tool or media to convey the teachings of Hinduism. Lontar is a classic literary work that contains ethical, aesthetic and religious aspects. Lontar Cakragni is a lontar which describes the problem of disease and treatment. In the Lontar Cakragni, it is described about the disease, how to cure it, the offerings are used. The method of determining informants using porvosive sampling. The educational values ​​that can be studied are the Value of Tattwa Education (Philosophy) in Lontar Cakragni, The Value of Ethical Education in Lontar Cakragni, Value of Ritual Education in Lontar Cakragni, Lontar Cakragni is one of the Tattwa lontars from the many lontars in Bali in the form of Speech. , The value of tattwa education and the value of ethical education. The value of tattwa education emphasizes more on the strength that arises from several elements in the human body, which later from the power that arises as a result of some of these elements of power can lead a person to spiritual ability and be able to bring someone to the attainment of deliverance